Specific Features of the Concepts of what “Immediate Environment”, Management Team, Methods for Its Selection, and One’s Own Managerial Role are for Executives of Different Management Levels - V. Sinyagin , Yury (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the results of studying the specific features of the concepts the executives of various management levels have about their “immediate environment," management team, methods for its selection, and their own managerial role. A huge array of 5240 executives is used to demonstrate the data of verifying the heuristicity of the three-component model of executives’ orientation in the space of organizational and one’s own tasks. Subjective models of forming effective management teams in the public administration system are presented. The specific ideas about the methods preferable to form an immediate environment are characterized. The new data are compared with the results of personal and professional diagnostics of executives and the level of their managerial position.